Deglacial water-table decline in Southern California recorded by noble gas isotopes - Alan M. Seltzer (Nature Portfolio, 2019)
In this study, a new analytical technique is employed to measure Kr and Xe isotopes in groundwater at high precision. These measurements indicate that gravitational signals of past water-table depth are preserved in ancient groundwater, representing a novel proxy for past terrestrial hydroclimate.